Magnetic resonance study of exchange-biased Ni/NiO nanoparticles. (24th April 2017) - Gandhi, Ashish Chhaganlal; Lin, Jauyn Grace
Abstract: Finite sized Ni/NiO nanoparticles (NPs) are prepared by oxidizing pure Ni-NPs in an ambient atmosphere with varying annealing time ( t A ). A synchrotron radiation x-ray diffraction technique was used to estimate the grain size, weight fraction and lattice parameters of Ni and NiO. The temperature ( T ) dependencies of effective g -factor and line-width of ferromagnetic resonance (FMR) spectra for a series of Ni/NiO NPs are determined. Three T -regions with different FMR behaviors T > 200 K, 200 > T > 130 K and T < 130 K are identified. In particular, for T < 200 K, the T -dependency of the g -factor reveals an evolution of exchange coupling between Ni and NiO due to the gradual oxidation of Ni NPs.